The Interrelation Between Language Anxiety and Self-Determined Motivation; A Mixed Methods Approach - Alamer, Abdullah; Almulhim, Fahad (Frontiers in Education, 2021)
The relationship between language anxiety and self-determined motivation has been examined from various aspects in the applied linguistics domain. However, the direction of the relationship tend to disagree. Some studies report positive correlation whereas others (and in most cases) show negative correlation. To address this issue, the present study attempted to evaluate in depth the relationship between these two variables. We first qualitatively examined the types of language anxiety students face during learning, and then assessed how motivational variables based on self-determination theory can predict these identified types of anxiety. The results showed that sense of competence and relatedness negatively predicted certain types of anxiety while controlled motivation positively predicted only the general language anxiety. However, perception of autonomy and autonomous motivation did not predict any sub-types of language anxiety while sense of relatedness positively predicted psychological anxiety. The findings are discussed in terms of their theoretical and educational implications for language learning.